Corrigendum: Azole-Resistance in Aspergillus terreus and Related Species: An Emerging Problem or a Rare Phenomenon? - Zoran, Tamara; Sartori, Bettina; Sappl, Laura; Aigner, Maria; Sánchez-Reus, Ferran; Rezusta, Antonio; Chowdhary, Anuradha; Taj-Aldeen, Saad J; Arendrup, Maiken C; Oliveri, Salvatore; Kontoyiannis, Dimitrios P; Alastruey-Izquierdo, Ana; et al. (Frontiers in microbiology, 2018)
[This corrects the article DOI: 10.3389/fmicb.2018.00516.].
Keywords: Aspergillus section Terrei; azoles; susceptibility profiles; Cyp51A alterations; cryptic species